2019
DOI: 10.1038/s41598-019-52969-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the 4p16 genomic locus and different types of congenital heart disease: results from adult survivors in the UK Biobank

Abstract: Congenital heart disease is the most common birth defect in newborns and the leading cause of death in infancy, affecting nearly 1% of live births. A locus in chromosome 4p16, adjacent to MSX1 and STX18, has been associated with atrial septal defects (ASD) in multiple European and Chinese cohorts. Here, genotyping data from the UK Biobank was used to test for associations between this locus and congenital heart disease in adult survivors of left ventricular outflow tract obstruction (n = 164) and ASD (n = 223)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Of the remaining 16 SNPs identified in the infant‐only case–control discovery analysis with p < 1 × 10 −5 , several are in genomic regions previously reported to be associated with atrial septal defects in other GWAS analyses, including 4p16 (Cordell et al, 2013; Pei et al, 2016; B. Zhao et al, 2014; L. Zhao et al, 2015). More recently, Córdova‐Palomero and colleagues studied adult survivors with CHDs in the UK Biobank and were the first to report an association between 4p16 and left ventricular outflow tract obstructions among 164 affected individuals versus 332,788 unaffected individuals (Córdova‐Palomera & Priest, 2019). In contrast, Cordell and colleagues did not find an association between 412 individuals with coarctation of the aorta, hypoplastic left heart syndrome, or aortic and mitral valve anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 16 SNPs identified in the infant‐only case–control discovery analysis with p < 1 × 10 −5 , several are in genomic regions previously reported to be associated with atrial septal defects in other GWAS analyses, including 4p16 (Cordell et al, 2013; Pei et al, 2016; B. Zhao et al, 2014; L. Zhao et al, 2015). More recently, Córdova‐Palomero and colleagues studied adult survivors with CHDs in the UK Biobank and were the first to report an association between 4p16 and left ventricular outflow tract obstructions among 164 affected individuals versus 332,788 unaffected individuals (Córdova‐Palomera & Priest, 2019). In contrast, Cordell and colleagues did not find an association between 412 individuals with coarctation of the aorta, hypoplastic left heart syndrome, or aortic and mitral valve anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Genome wide association studies have found loci that meet standard statistical criteria for significance, but the loci identified have not yet overlapped or been strongly validated. New well-powered studies utilizing the UK Biobank data have shown convincing genetic effects on cardiac valve and aortic endophenotypes that can be directly related to left heart and outflow tract development [ 52 , 53 ]. In a striking recent example of this research strategy, Tcheandjieu et al [ 53 ] used MRI imaging data from the UK Biobank to estimate ascending aortic diameters, mapped common gene variant associations, and used those results to make a polygenic score.…”
Section: Complex Inheritancementioning
confidence: 99%
“…003968 June 2023 259 increased risk of adult-onset cardiovascular disease, [3][4][5] neuropsychiatric disease, 6 and cancer. 7 CHD is observed to be highly heritable, [8][9][10][11][12] but the power to identify inherited genetic risk has been primarily limited to analysis of common variants in small cohorts. Familial clustering of specific malformations indicates that up to 90% of the risk for CHD is attributable to heritable genetic variation 8,9 which includes common [10][11][12] and rare 13,14 variants linked to specific CHD phenotypes.…”
mentioning
confidence: 99%
“…7 CHD is observed to be highly heritable, [8][9][10][11][12] but the power to identify inherited genetic risk has been primarily limited to analysis of common variants in small cohorts. Familial clustering of specific malformations indicates that up to 90% of the risk for CHD is attributable to heritable genetic variation 8,9 which includes common [10][11][12] and rare 13,14 variants linked to specific CHD phenotypes. Mendelian inheritance of deleterious protein-coding variation in any individual gene accounts for <1% of the burden of CHD, 15 and when Mendelian forms of CHD are combined they identify <10% of the risk for disease.…”
mentioning
confidence: 99%